Tailored Versus Standard Hydration to Prevent Acute Kidney Injury After Percutaneous Coronary Intervention: Network Meta‐Analysis - Francesco Moroni; Luca Baldetti; Conrad Kabali; Carlo Briguori; Mauro Maioli; Anna Toso; Emmanouil S. Brilakis; Hitinder S. Gurm; Rodrigo Bagur; Lorenzo Azzalini (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Contrast‐induced acute kidney injury (CI‐AKI) is a serious complication after percutaneous coronary intervention. The mainstay of CI‐AKI prevention is represented by intravenous hydration. Tailoring infusion rate to patient volume status has emerged as advantageous over fixed infusion‐rate hydration strategies. Methods and Results A systematic review and network meta‐analysis with a frequentist approach were conducted. A total of 8 randomized controlled trials comprising 2312 patients comparing fixed versus tailored hydration strategies to prevent CI‐AKI after percutaneous coronary intervention were included in the final analysis. Tailored hydration strategies included urine flow rate–guided, central venous pressure–guided, left ventricular end‐diastolic pressure–guided, and bioimpedance vector analysis–guided hydration. Primary endpoint was CI‐AKI incidence. Safety endpoint was incidence of pulmonary edema. Urine flow rate–guided and central venous pressure–guided hydration were associated with a lower incidence of CI‐AKI compared with fixed‐rate hydration (odds ratio [OR], 0.32 [95% CI, 0.19–0.54] and OR, 0.45 [95% CI, 0.21–0.97]). No significant difference in pulmonary edema incidence was observed between the different hydration strategies. P score analysis showed that urine flow rate–guided hydration is advantageous in terms of both CI‐AKI prevention and pulmonary edema incidence when compared with other approaches. Conclusions Currently available hydration strategies tailored on patients' volume status appear to offer an advantage over guideline‐supported fixed‐rate hydration for CI‐AKI prevention after percutaneous coronary intervention. Current evidence suggests that urine flow rate–guided hydration as the most convenient strategy in terms of effectiveness and safety.